Construct Validity Test of Academic Resilience Inventory (ARI): A Potential Scale for Assessing Students’ Academic Resilience During Pandemic COVID-19 - Teguh Fachmi; Dalis Ravida Kustiwa (Da'wa Faculty of Islamic State University Salatiga, 2022)
This study aims to test the reliability and validity of the Academic Resilience Inventory (ARI), which was developed by Samuel (2004) for the Indonesian context. The inventory adaptation procedure that the researchers did in this research refers to the journal Guidelines for the Process of Cross-Cultural Adaptation of Self-Report Measures (Beaton, 2000). The total amount of sample used in this study was 200 students of Public Vocational School 1 Pandeglang, taken by using accidental sampling. To test the validity of the measurement inventory, the researcher used Confirmatory Factor Analysis (CFA) with Lisrel software. The result revealed that, in general, the Academic Resilience Inventory (ARI) by Samuel (2004) is significantly unidimensional, meaning it only measures the construct of the academic resilience inventory. However, in the result of CFA, the validity test known that item no.8 on the intelligence factor, item no. Forty on temperamental factors, items no. 2, 14, 25, 26, and 28 on social relations factors, item no. Three on the factor of family relations, item no. 6 on academic factors are invalid. Further psychometric properties analysis and education are described.